Dopamine as the coating agent and carbon precursor for the fabrication of N-doped carbon coated Fe3O4 composites as superior lithium ion anodes - Lei, Cheng; Han, Fei; Li, Duo; Li, Wen-Cui; Sun, Qiang; Zhang, Xiang-Qian; Lu, An-Hui (Nanoscale, 2013)
Dopamine is an excellent and flexible agent for surface coating of inorganic nanoparticles and contains unusually high concentrations of amine groups. In this study, we demonstrate that through a controlled coating of a thin layer of polydopamine on the surface of α-Fe(2)O(3) in the dopamine aqueous solution, followed by subsequent carbonization, N-doped carbon-encapsulated magnetite has been synthesized and shows excellent electrochemical performance as anode material for lithium-ion batteries. Due to the strong binding affinity to iron oxide and excellent coating capability of this new carbon precursor, the conformal polydopamine derived carbon is continuous and uniform, and its thickness can be tailored. Moreover, due to the high percentage of nitrogen content in the precursor, the resulting carbon layer contains a moderate amount of N species, which can substantially improve the electrochemical performance. The composites synthesized by this facile method exhibit superior electrochemical performance, including remarkably high specific capacity (>800 mA h g(-1) at a current of 500 mA g(-1)), high rate capability (595 and 396 mA h g(-1) at a current of 1000 and 2000 mA g(-1), respectively) and excellent cycle performance (200 cycles with 99% capacity retention), which adds to the potential as promising anodes for the application in lithium-ion batteries.